The Effect of Using Online Learning Platform on Academic Performance of Plant Morphology Course - Veronika Turnip; Ely Djulia (Jurnal Pendidikan Biologi Undiksha, 2022)
This study aims to find out the  effect of using online learning platform on academic  performance  of plant morphology course. The subjects in this study students majoring in Biology at Universitas Negeri Medan. This research is a study using is descriptive with a quantitative approach. The results showed that Students are declared capable of using online learning platforms indicated by the average results of internet searching 88% hypertext navigation 87%, content Evaluation 85% and Knowledge Assembly 81%. (2) Biology student understanding on the final test score is said to be in the very high category with an average of 89.9% and the mid-term grades are categorized as moderate with an average of 85.17%. (3) There is a correlation between student learning literacy and maser the concept through the online learning platform with a correlation of recount = 0.71297.  So students have been able to take advantage of use the online learning platform well in plant morphology course